The economic effects of international sanctions: An event study - Jerg Gutmann; Matthias Neuenkirch; Florian Neumeier (Universität Trier, Fachbereich IV - Volkswirtschaftslehre, 2021)
Although international sanctions are a widely used instrument of coercion, their economic effects are still not well-understood. This study uses a novel dataset and an event study approach to evaluate the economic consequences of international sanctions, thereby visualizing pre-treatment and treatment dynamics in countries subject to sanctions. Our analysis focuses on the effects of sanctions on GDP growth as well as on various transmission channels through which sanctions suppress economic activity. We document a significant negative effect of sanctions on the growth rate of GDP and its components (consumption and investment) as well as on trade and foreign direct investment. Given that sanctions exert their adverse effect over the first years of a sanction episode and that sanctioned countries fail to recover during or immediately after the episode, we demonstrate the usefulness of sanctions as a political instrument of coercion. Long-lasting sanctions regimes, however, may not provide the political incentives needed to force additional concessions.
Keywords: F43; F51; F52; F53; O43; O47; 330; Economic growth; event study; international sanctions; transmission channels